If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(b + 3) = 4b Reorder the terms: 8(3 + b) = 4b (3 * 8 + b * 8) = 4b (24 + 8b) = 4b Solving 24 + 8b = 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. 24 + 8b + -4b = 4b + -4b Combine like terms: 8b + -4b = 4b 24 + 4b = 4b + -4b Combine like terms: 4b + -4b = 0 24 + 4b = 0 Add '-24' to each side of the equation. 24 + -24 + 4b = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 4b = 0 + -24 4b = 0 + -24 Combine like terms: 0 + -24 = -24 4b = -24 Divide each side by '4'. b = -6 Simplifying b = -6
| (5x+6)(2x-7)= | | y=20/3x-1 | | 1.5x-8.4=0.4+2.6x | | 3x(87*2)=0 | | 4x^2-19x+18=-6x+8 | | 20x-3y=1 | | x^2-x-16=-5x-4 | | 17x-13=-4x+47+15x | | 18x+125=12x+200 | | 18x=12x | | x+3x+15=0 | | 2cos^2=1+2sin^2x | | p=k-3/2k+5 | | 1000000=-40900x+1400000 | | 11=8-3x | | x^4-18x^2-16x-15=0 | | ln(5x-7)=6 | | (x-2c)(2x+c)+cx= | | 2y/5=12 | | 6c+2A=38 | | A=1/2(4)(4) | | 72/18 | | A=1/2(4/5)(4/5) | | A=1/2(16)(12) | | (6x-7)=(2x-7) | | 3b+b=b+12 | | A=1/2(14)(14) | | x+2/3=0 | | 9-4(2)(1)= | | 800+0.25x=x | | n+11=17 | | A=1/2(32)(32) |